2012
DOI: 10.1136/bmjqs-2012-000800
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a hospital-wide hand hygiene initiative on healthcare-associated infections: results of an interrupted time series

Abstract: Background: Evidence that hand hygiene (HH) reduces healthcare-associated infections has been available for almost two centuries. Yet HH compliance among healthcare professionals continues to be low, and most efforts to improve it have failed. Objective: To improve healthcare workers' HH, and reduce healthcare-associated infections. Design: 3-year interrupted time series with multiple sequential interventions and 1-year post-intervention follow-up. Setting: Teaching hospital in rural New Hampshire. Interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 31 publications
4
78
0
7
Order By: Relevance
“…Other studies have demonstrated that the presence of leadership appeared to play a key role in improving hand hygiene adherence. 23,24 Moreover, a recent Japanese nationwide survey demonstrated higher safety centeredness was associated with regular use of standard infection prevention practice. 25 Consistent with a previous study, improving hand hygiene adherence cannot be simply achieved by improving infrastructure (eg, introduction of portable alcohol-based hand rub) alone, but it depends on altering healthcare worker behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that the presence of leadership appeared to play a key role in improving hand hygiene adherence. 23,24 Moreover, a recent Japanese nationwide survey demonstrated higher safety centeredness was associated with regular use of standard infection prevention practice. 25 Consistent with a previous study, improving hand hygiene adherence cannot be simply achieved by improving infrastructure (eg, introduction of portable alcohol-based hand rub) alone, but it depends on altering healthcare worker behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown a long-term effect of hygiene interventions on compliance with hygiene guidelines (Kirkland et al 2012;Tromp et al 2012;Mernelius et al 2013c;Biswal et al 2014) whereas others have demonstrated the opposite (Gould & Chamberlain 1997). All studies reporting on a long-term effect were multimodal, whereas the study reporting no long-term effect only featured a single intervention.…”
Section: Interventions To Improve Compliance With Hygiene Guidelinesmentioning
confidence: 97%
“…The most successful way to accomplish this has proven to be by applying a multimodal hygiene intervention (Pittet et al 2000;Kirkland et al 2012;Tromp et al 2012;Mernelius et al 2013c;Biswal et al 2014). Hygiene interventions that are multidisciplinary, including all disciplines of HCWs, also physicians, also appear to be more successful (Mernelius et al 2013c).…”
Section: Interventions To Improve Compliance With Hygiene Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations